Will Coronavirus Disease 2019 Become Seasonal? - Kanzawa, Mia (J Infect Dis, 2020)
This manuscript explores the question of the seasonality of severe acute respiratory syndrome coronavirus 2 by reviewing 4 lines of evidence related to viral viability, transmission, ecological patterns, and observed epidemiology of coronavirus disease 2019 in the Southern Hemispheres’ summer and early fall.